Effects of crude polysaccharides from marine macroalgae on the adhesion and biofilm formation of Pseudomonas aeruginosa and Staphylococcus aureus - Zammuto V. Vincenzo; Rizzo M. G. Maria Giovanna; Span`o A. Antonio; Spagnuolo D. Damiano; Morabito M. Marina; Di Martino A. Antonio; Manghisi A. Antonio; Genovese G. Giuseppa; Guglielmino S. Salvatore; Calabrese G. Giovanna; Capparucci F. Fabiano; Gervasi C. Claudio; et al. (2022, 2022)
Title screen